2010
DOI: 10.1590/s0037-86822010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of rabies virus isolated from bovines and equines between 2007 and 2008, in the States of São Paulo and Minas Gerais

Abstract: Introduction: Rabies is an acute disease of the central nervous system and is responsible for the deaths of thousands of humans, wild animals and livestock, particularly cattle, as well as causing major economic losses. This study describes the genetic characterization of rabies virus variants that circulate in Desmodus rotundus populations and are transmitted to herbivores. Methods: Fifty rabies virus isolates from bovines and equines in the States of São Paulo and Minas Gerais, Brazil, were genetically chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
1
8
0
2
Order By: Relevance
“…Our study revealed that at least 4 phylogenetic lineages of RABV are circulating in vampire bat populations in Peru; these lineages appeared to display distinctive spatiotemporal dynamics across their geographic ranges. Three of the lineages had wide geographic distributions in Peru and recent and historical relationships linked to rabies outbreaks occurring in other parts of South America (24,(26)(27)(28)(29)(30)(31)(32). Dissemination of vampire bat-associated RABV appears to be gradual rather than involving long-distance dispersal events, as might be expected by the absence of long-distance migration and small home range of the reservoir species (33,34).…”
Section: Discussionmentioning
confidence: 93%
“…Our study revealed that at least 4 phylogenetic lineages of RABV are circulating in vampire bat populations in Peru; these lineages appeared to display distinctive spatiotemporal dynamics across their geographic ranges. Three of the lineages had wide geographic distributions in Peru and recent and historical relationships linked to rabies outbreaks occurring in other parts of South America (24,(26)(27)(28)(29)(30)(31)(32). Dissemination of vampire bat-associated RABV appears to be gradual rather than involving long-distance dispersal events, as might be expected by the absence of long-distance migration and small home range of the reservoir species (33,34).…”
Section: Discussionmentioning
confidence: 93%
“…However, lately, its presence has been expanding to urban centres in Brazil [3234]. It has been reported in cities such as Belo Horizonte city, the third largest Brazilian city, and in Sao Paulo state [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…A raiva é uma doença aguda, progressiva e fatal, responsável pela morte de milhares de humanos, animais silvestres e animais de criação -especialmente bovinos (MACEDO et al, 2010). A enfermidade é causada por um vírus RNA neurotrópico pertencente à família Rhabdoviridae, gênero Lyssavirus e sua transmissão costuma ser percutânea, através da mordedura de animais infectados (BRITO et al, 2011;GOMES et al, 2007).…”
Section: Introductionunclassified